Fluorescence of a triple-stranded helicate iron(iii) complex from a novel bis-β-diketone ligand: synthesis, structure and spectroscopic studies. Issue 35 (27th July 2016) - Zou, Fang; Tang, Xiao; Huang, Yuhong; Wan, Shigang; Lu, Fa; Chen, Zhe-Ning; Wu, Anan; Zhang, Hui
Abstract : The intensity of fluorescence was highly enhanced when the complex [Fe2 (BOBA)3 ] was formed, which was a consequence of the inversion emission mechanism from n–π* states for the ligand to π–π* states for the iron helicate. Abstract : A new bis-β-diketone ligand, 3, 5-bis-(3-oxobutanoyl)benzoic acid (BOBA), has been designed and prepared for the self-assembly of the dinuclear triple-helical Fe(iii ) complex Fe2 (BOBA)3 and the mononuclear Cd(ii ) complex Cd(BOBA)2 (py)3 . The ligand BOBA was proved to exist in the enol form both in the solid-state and in solution by single crystal X-ray analysis and 1 H and 13 C NMR studies. X-ray crystallographic analysis reveals that dinuclear Fe(iii ) complexes consist of a triple helicate, within which the Fe(iii ) ions are in pseudo-octahedral environments, bound to three diketonate units from three different ligands, while Cd(BOBA)2 (py)3 features a mononuclear motif with the Cd(ii ) center taking a distorted pentagonal pyramidal geometry that is filled by two carboxylates from two BOBA ligands and three pyridines. The photophysical properties of the ligand and the two complexes are thoroughly investigated. Compared with the free ligand BOBA and Cd(BOBA)2 (py)3, the helicate Fe2 (BOBA)3 displays much stronger fluorescence upon excitation at 289 nm, representing a rare case of a luminescent transition metal coordination compound without a d 10 configuration. Time-dependent density functional theory (TD-DFT) calculations indicate that transformation from an n–π* to a π–π* character is responsible for the fluorescence enhancement observed for Fe2 (BOBA)3 .